Infratuberositary slope-decreasing anterior closed wedge proximal tibial osteotomy is safe and shows rapid bone healing - Schuster, Philipp; Mayer, Philipp; Schubert, Ilona; Leiprecht, Janina; Micioi, Gregoire; Reuter, Benoit; Richter, Jörg; Dickschas, Jörg (Knee Surgery Sports Traumatology Arthroscopy, 2024)
Purpose: Different techniques of slope-decreasing anterior closed-wedge proximal tibial osteotomy (ACW-PTO) have been described. To determine the peri- and post-operative complication rate and obtain data on bone healing in ACW-PTO with an infratuberositary approach. Methods: A total of 170 consecutive ACW-PTO of two sports-orthopaedic centres were retrospectively evaluated (97 and 73, respectively). Routine follow-up was performed after 6 weeks and was available in 166 cases (97.7%). Medical charts and x-rays of these cases were reviewed with regard to technique-specific complications. Lateral x-rays (n = 155) at 6 weeks post-operatively were evaluated with regard to bone healing (completely healed, partially healed or with no or delayed signs of bone healing). A multivariate binary logistic regression was performed to detect factors that influence bone healing. Results: There was one case with haematoma and superficial wound-healing problems after 5 weeks with progression to a deep wound infection and revision surgery (plate exchange) at 11 weeks after the index surgery. One case with delayed bone healing was treated with plate exchange combined with revision anterior cruciate ligament reconstruction after 4 months. The further course of both cases was uneventful. No other complications were observed. Therefore, the overall complication rate was 1.2% (2 out of 166). Radiologic evaluation at 6 weeks showed complete healing in 104 cases (67.1%), partial healing in 50 cases (32.3%) and delayed healing only in the aforementioned case (0.6%), respectively. All cases of partial healing showed complete healing at 12 weeks. In regression analysis, a completely closed osteotomy (odds ratio [OR] = 3.5, p = 0.003) and compression of the osteotomy (OR = 2.5, p = 0.026) were significantly associated with complete bone healing at 6 weeks. Conclusions: ACW-PTO using an infratuberositary approach is very safe with regard to complication rate and shows rapid bone healing. The osteotomy should be completely closed and compression should be applied for optimal bone healing. Study Design: Case series with pooled data of two centres. Level of Evidence: Level 4.
CRIS-Team Scopus Importer:2025-02-04
Keywords: anterior cruciate ligament; complication; osteotomy; PTS; slope